2022
DOI: 10.3390/su142316159
|View full text |Cite
|
Sign up to set email alerts
|

Devising a Mechanism for Analyzing the Barriers of Blockchain Adoption in the Textile Supply Chain: A Sustainable Business Perspective

Abstract: The adoption of blockchain technology (BCT) in a supply chain holds great potential for textile industries by executing transactions among stakeholders in a most reliable and verifiable way. Textile industries in emerging economies, like Pakistan, confront severe economic pressures and uncertain environment and strive to achieve sustainable supply chain excellence through blockchain implementation. This study is an initiative to analyze the key barriers in adopting BCT-related practices within the textile indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Based on stakeholder theory, firms that prioritize environmental responsibility can better manage their relationships with stakeholders and gain their support [8,47], which ultimately affects their performance. This is because stakeholders are increasingly concerned about the performance of firms in relation to environmental responsibility [48].…”
Section: Theoretical Hypothesis 221 Green Innovation and Financial Pe...mentioning
confidence: 99%
“…Based on stakeholder theory, firms that prioritize environmental responsibility can better manage their relationships with stakeholders and gain their support [8,47], which ultimately affects their performance. This is because stakeholders are increasingly concerned about the performance of firms in relation to environmental responsibility [48].…”
Section: Theoretical Hypothesis 221 Green Innovation and Financial Pe...mentioning
confidence: 99%
“…But blockchain technology can ensure sustainable supply chain excellence by lowering human errors, detecting unethical suppliers, minimising cost of supply chain failures and transactional times. In contrast, technological and system related barriers, human resource and R&D barriers hinder the adoption of blockchain in the industry [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bhushan et al [ 30 ] noted that blockchain may also lead to user privacy disclosure because the data on the public chain may be stolen. In addition, Nazam et al [ 31 ] evaluated blockchain technology-related barriers by developing an integrated model in the textile supply chain. They suggested that top-level management should pay more attention to and encourage bottom-level management to adopt technological and system-related practices and that technological transformation in the textile and apparel industry would be complicated by a number of constraints.…”
Section: Literature Reviewmentioning
confidence: 99%